The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.18860/em.v8i1.4965
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Profitabilitas, Dividend Policy,leverage, Dan Keputusan Investasi Terhadap Nilai Perusahaan Konstruksi Di Bursa Efek Indonesia

Abstract: Penelitian ini bertujuan untuk menguji pengaruh profitabilitas, <em>dividend policy</em>, <em>leverage</em>, dan keputusan investasi terhadap nilai perusahaan konstruksi yang terdaftar di Bursa Efek Indonesia. Populasi dalam penelitian ini adalah seluruh perusahaan konstruksi yang terdaftar di Bursa Efek Indonesia (BEI). Dalam penelitian ini ditetapkan teknik pengambilan sampel dengan menggunakan <em>purposive sampling,</em> dan berdasarkan kriteria yang telah ditentukan mak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
1
1
0
1
Order By: Relevance
“…The level of debt owned by the company is not a major problem for investors if the composition of debt owned by the company is still in a reasonable condition or amount. This hypothesis confirms the three previous studies, namely research conducted by Ogolmagai (2013) which states that leverage has no significant effect on firm value, the second is Novari and Lestari (2016) which revealed that leverage has no effect on firm value, and the last one is Nugroho. and Abdani (2017) which states that leverage has no effect on firm value.…”
Section: Resultssupporting
confidence: 89%
“…The level of debt owned by the company is not a major problem for investors if the composition of debt owned by the company is still in a reasonable condition or amount. This hypothesis confirms the three previous studies, namely research conducted by Ogolmagai (2013) which states that leverage has no significant effect on firm value, the second is Novari and Lestari (2016) which revealed that leverage has no effect on firm value, and the last one is Nugroho. and Abdani (2017) which states that leverage has no effect on firm value.…”
Section: Resultssupporting
confidence: 89%
“…The results also show that leverage does not affect the value of manufacturing companies. This is because investors need further information in terms of how management uses its company's capital to improve company performance (Nugroho and Fadlil, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Hasil penelitian Antoro (2018) menyimpulkan bahwa profitabilitas berpengaruh signifikan positif terhadap nilai perusahaan. Sedangkan Nugroho et al (2017) Menurut penelitian sebelumnya yang dilakukan oleh Krisnando et al (2019) menyatakan bahwa keputusan pendanaan, Leverage, Growth Opportunity menunjukan hasil berpengaruh secara simultan terhadap nilai perusahaan. Hasil tersebut sesuai dengan hasil penelitian yang dilakukan oleh Oktavia (2020) dengan judul penelitian pengaruh keputusan investasi, keputusan pendanaan, dan kebijakan dividen terhadap nilai perusahaan.…”
Section: Gambar 1 Grafik Rata-rata Nilai Perusahaanunclassified